PERCEPTIONS AND THE IMPLEMENTATION OF CONTINUING PROFESSIONAL DEVELOPMENT THROUGH INNOVATION AMONG ENGLISH TEACHERS - Teguh Kasprabowo (Dinamika Bahasa dan Budaya, 2019)
This study was part of a larger study on teachers’ continuing professional development (CPD) of English teachers in Ungaran Sub-districts. This study aimed to explain the perceptions and the implementation of CPD through innovation done by the respondents. This study employed qualitative case study. To gain the data, 21 teachers were involved in this study,17 of them were certified teachers and later selected as the respondents. 7 teachers were later selected conveniently for the interview. The study showed that there was awareness of the teachers on the importance of making innovation in their work. However, after being interviewed, only few of them made innovation in their teaching and learning process. Keyword: CPD, innovation, awareness